Yudicial Review Omnibus Law Dalam Melindungi Pekerja dan Mengembangkan Investasi di Indonesia - Muhammad Eko Purwanto; Efridani Lubis (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2022)
The urgency of the Omnibus Law as a solution to investment regulation in Indonesia is because Indonesia is a legal state that has the role of a welfare state. In addition, omnibus law is also a concept of a legal product that functions to consolidate various themes, materials, subjects, and laws and regulations in each sector to become one extensive and holistic legal product. With the establishment and promulgation of the omnibus, it is hoped that it will facilitate investment for investors, which will impact increasing the economy as people's prosperity. Omnibus law as the rule of law will embody the rule of law in the economic aspect as legal certainty, benefit, and justice. In addition, the Omnibus Law is also expected to protect the Indonesian workforce in the future, such as regulations regarding worker status, wages, working hours, compensation for layoffs, and the use of foreign workers. Directly or indirectly.